Hubungan Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Penghindaran Pajak Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia 2010-2019 - Sari, Putri Rukmana; Astuti, Titiek Puji; Siddiq, Faiz Rahman; Herawati, Nurul (Jurnal Akuntansi dan Pajak, 2023)
The study aims to determines the influence of profitability, leverage,and firm size for tax avoidance on mining companies listed on the Indonesia Stock Exchange (IDX) 2010-2019 period. This study uses secondary data, Population in this research is all of the mining companies listed in IDX. Eighty samples used as samples observations. Method sampling technique that used is purposive sampling with regression panel data as analysis. The result in this research show that profitability has negative influence on tax avoidance meaning that the higher the profitability, the lower the occurrence of tax avoidance and vice versa. but the result in this research show that leverage, and firm size have no influence on tax avoidance. Keywords : Tax Avoidance, Profitabilitas, Leverage, Firm Size Maksimum 5 kata kunci dipisahkan dengan tanda koma.